Analysis Of Pregnant Women's Knowledge About Hepatitis B Regarding The Implementation Of Laboratory Examinations At Tulungagung University D3 Midwifery Study Program In 2024 - Siti Maryam; Ernawati Tri Handayani (Journal for Quality in Women's Health, 2025)
Liver disease caused by the Hepatitis B virus is a major problem in the world, with an estimated 400 million people carrying this virus. attacks all ages, genders and races throughout the world. About 5% of the world's population suffers from hepatitis B without symptoms. The prevalence in Indonesia is around 5-17%. Pregnant women who are positive for hepatitis B infection are at greater risk of giving birth prematurely, having low birth weight (BBLR) and experiencing disability. Women who are detected to have hepatitis B e-antigen (HBeAg) are the most infectious. In reality, not all pregnant women know the importance of hepatitis B screening. Not all pregnant women are routinely screened for hepatitis B, so it is only discovered that pregnant women have hepatitis B at 28 to 37 weeks of pregnancy.